SISTEM OPTIMALISASI ENERGI LISTRIK DENGAN INTERNET OF THINGS ASSISTED ARTIFICIAL INTELLEGANCE - Pratama, M Ghalu; Alfarizal, Niksen (JURNAL TELISKA, 2025)
In the current digital era, the increasing awareness of energy efficiency, coupled with high operational costs and environmental impacts, has become a primary concern. Internet of Things (IoT) and Artificial Intelligence (AI) technologies offer solutions to optimize electricity consumption through real-time data collection and advanced analytics. This study aims to explore the integration of IoT and AI in smart energy management systems to reduce costs and environmental impact. By employing machine learning algorithms, the research will predict electricity consumption and provide energy efficiency recommendations. It is anticipated that this system will enhance energy efficiency, lower operational costs, and contribute to environmental sustainability. This study is expected to make a significant contribution to the development of innovative solutions for electricity optimization based on IoT and AI.